Preparation, thermal, magnetic and microwave absorption properties of thermoplastic natural rubber matrix impregnated with NiZn ferrite nanoparticles - Flaifel, Moayad Husein; Ahmad, Sahrim; Abdullah, Mustaffa; Rasid, Rozaidi; Shaari, Abdul Halim; El-Saleh, Ayman A.; Appadu, Sivanesan (Elsevier, 2014)
In this research, NiZn ferrite nanoparticles were incorporated in thermoplastic natural rubber matrix (TPNR) as reinforcing magnetic nanofiller by melt blending technique. TPNR was prepared from high-density polyethylene (HDPE), natural rubber (NR) and liquid natural rubber (LNR) in a ratio of 70:20:10 and later impregnated with 4, 8, 12 (wt%) of NiZn ferrite nanoparticles. Thermal stability, temperature dependence of coercivity and microwave absorption characteristics of the nanocomposite samples were investigated using thermogravimetric analyser (TGA), vibrating sample magnetometer (VSM) and vector network analyser (VNA), respectively. The results showed that the thermal stability of the nanocomposite samples has increased with increasing filler content in the TPNR matrix. Temperature dependence of coercivity for pure NiZn ferrite and nanocomposite samples exhibited immeasurable values below blocking temperature (TB), above which an abrupt increase was observed. In addition, the microwave absorption results showed multi-absorbing peaks characteristic with a great enhancement attained for 12 wt% nanocomposite at a sample thickness of 7 mm with a potential application in the X-band frequency.